American Indian Women Cancer Survivors’ Coping with Depressive Symptoms - Burnette, Catherine E. (J Psychosoc Oncol, 2018)
OBJECTIVE: Depressive symptoms have been identified as a primary predictor of quality of life among cancer patients. Depression and cancer are co-occurring and disproportionately elevated for American Indian and Alaska Native (AI/AN) women.. The purpose of this article is to examine American Indian (AI) women cancer survivors’ coping mechanisms for depressive symptoms. RESEARCH APPROACH: The methodology included a qualitative descriptive approach with conventional content analysis to examine the coping strategies of AI women cancer survivors associated with depressive symptoms. The interview guide was semi-structured and developed in collaboration with a community advisory board (CAB). Data-derived qualitative analysis was used to generate codes inductively from the data. PARTICIPANTS: A sample of 43 AI women cancer survivors (n=14 cervical cancer, n=14 breast cancer, and n=15 other cancers) from the Northern Plains region, in the state of South Dakota were interviewed. Data were collected from June 2014 to February 2015. METHODOLOGICAL APPROACH: Qualitative content analysis was used for data analysis, which allowed themes to emerge inductively from the data. Analysis revealed 430 preliminary codes. After de-briefing, validation, and discussion among co-authors, these were then sorted into 67 codes. Member checks with all available participants were conducted to minimize misinterpretation. FINDINGS: A total of 26 participants (62%) indicated they had feelings of depression since their cancer diagnosis. Women coped with depressive feelings by (a) participating in faith traditions; (b) seeking creative and positive outlets; (c) martialing family and social support; and (d) keeping busy with other life activities. INTERPRETATION: AI women experienced depressive symptoms following a cancer diagnosis and used a variety of positive coping mechanisms to create personal meaning. IMPLICATIONS FOR PSYCHOSOCIAL PROVIDERS OR POLICY: AI women may need unique support following a cancer diagnosis, and interventions should incorporate AI beliefs and traditions, such as storytelling and talking with family and community members.